A 3-D Wells–Dawson phosphotungstate hybrid material modified by Na+ and a bi-copper organic complex linker, and its photo-/electro-catalytic properties. Issue 21 (2nd November 2017) - Lv, Jinghua; Yu, Kai; Zhang, He; Wang, Chunmei; Wang, Chunxiao; Zhou, Baibin
Abstract: An inorganic–organic hybrid material based on Dawson polyoxometalates, [Na2 {Cu I 2 (bim)2 }2 (P2 W18 O62 )]·2H2 O (bim = biimidazole) (1 ), has been hydrothermally synthesized and fully characterized. In1, each P2 W18 cluster as a hexa-node ligand connects to six adjacent Dawson clusters via six Na1 ions to generate a pure inorganic 2-D layer, further joined by bimetal–organic segments [Cu2 (bim)2 ] 2+ to form a 3-D inorganic–organic hybrid framework with channels. The structure can be simplified to 3, 8-connected 3-D networks with (4 3 )(4 18 ·6 24 ·8 3 ) topology, which shows bifunctional electrocatalytic performance for oxidation of ascorbic acid (AA) and reduction of nitrite (NO2 − ), and high-efficient degradation ability for three typical dyes under UV light irradiation. Abstract :